Appeal for Review: Current Limits and Need for Reformulation in the Central Tax Administration - Camacho Guamán, María Isabel (Iuris Dictio, 2026)
The Public Administration may issue acts with final effects, yet these may contain errors that affect the rights of individuals. This study examines the extraordinary appeal for review, assessing whether it serves to correct such errors or, conversely, infringes upon principles such as legal certainty and legitimate expectation. The analysis highlights the tension between the public interest and the protection of individual rights, noting a weak regulatory framework for this remedy in tax matters, which may lead to its discretionary application. It concludes that such practice not only undermines fundamental guarantees but also violates due process within administrative proceedings, generating legal uncertainty for citizens.